2021
DOI: 10.1088/1361-6587/abf85f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energetic particles on the density-gradient-driven collisionless trapped electron mode instability in tokamak plasmas

Abstract: We investigate analytically the effects of energetic particles (EPs) on the instability of the density-gradient-driven collisionless trapped electron mode (CTEM) through linear gyrokinetic theory and bounce kinetic theory in tokamak plasmas. The effects of EPs, including fusion-born alpha particles and neutral-beam-injection-driven beam ions, on the CTEM instability are compared for the dynamic model with slowing-down (SD) and equivalent Maxwellian (EM) equilibrium EP distribution functions and dilution model.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…For α particles, their equilibrium distribution functions are described by the SD distribution function as in [54] in the limit of shearless slab geometry. The total perturbed number density of α particles has been derived in [35] in detail, and we just use it as…”
Section: Dispersion Relation Of Ctem Instability With Helium Ash and ...mentioning
confidence: 99%
See 3 more Smart Citations
“…For α particles, their equilibrium distribution functions are described by the SD distribution function as in [54] in the limit of shearless slab geometry. The total perturbed number density of α particles has been derived in [35] in detail, and we just use it as…”
Section: Dispersion Relation Of Ctem Instability With Helium Ash and ...mentioning
confidence: 99%
“…where the concentrations of species j and α particles are expressed as f j = n 0 j /n 0e and f α = n 0α /n 0e , respectively. For simplicity of calculation, it should be stressed that the higher order term proportional to ω * e ω r (1 + η e ) in the non-resonant part of trapped electron perturbed density can be dropped in order to solve the linear dispersion rather than quadratic dispersion equation as used in [35,55]. Then, the normalized real frequency ωr = ω r / v thH /R and growth rate γk = γ k / v thH /R are given as…”
Section: Dispersion Relation Of Ctem Instability With Helium Ash and ...mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that TEM drives low-level transport of alpha particles 39 . The resonant interactions between energetic particles and micro-instability will be significant for ITG modes 40 , 41 but not for TEM and ETG modes because the propagation directions are opposite 42 . Therefore, interactions between energetic particles and TEM/ETG turbulence are expected to be weak.…”
Section: Discussionmentioning
confidence: 99%